FLEXIBLE FLOOR BUILDINGS AND SEISMICITY - Mirzababayeva Saxiba Mirzaakbarovna (Journals Park Publishing, 2024)
The article talks about the development of methods for increasing the seismic resistance of existing buildings by using elements of parametric design, design solutions for active seismic protection devices using local raw materials, generative design, kinetic architecture, microfabrication, parametric solutions. The article uses scientific research by a number of scientists [1-30].
Keywords: Seismic protection systems, seismic adaptation, adaptive systems, generative design, kinetic architecture, parametric modeling, IT in construction production, digitalization of construction production, ecology, construction practice, economics, service life accounting, duration, quality.